2019
DOI: 10.1186/s12954-019-0288-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heat and freeze-thaw cycling on naloxone stability

Abstract: Purpose The availability of take home naloxone (THN) was increased for Canadians in 2016, including access to kits via pharmacies. Unlike typical over-the-counter (OTC) and prescription drugs, THN kits may be stored in non-standard conditions, including in vehicles, backpacks, and out of doors. To evaluate whether these non-standard storage conditions affect stability, we investigated the impact of heat and freeze-thaw cycling on naloxone hydrochloride stability. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…For example, CT state law dictates that naloxone vending machines located outdoors (and therefore available 24/7) be temperature-regulated in accordance with commercial storage suggestions [ 70 ]. However, laboratory experiments have shown that even extreme temperatures far above or below the suggested storage limits do not reduce the potency of naloxone [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, CT state law dictates that naloxone vending machines located outdoors (and therefore available 24/7) be temperature-regulated in accordance with commercial storage suggestions [ 70 ]. However, laboratory experiments have shown that even extreme temperatures far above or below the suggested storage limits do not reduce the potency of naloxone [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AUC inf ratio was 1.08 in favor of the dry powder, indicating about 8% higher bioavailability than for the comparator Narcan nasal spray. Powder has an advantage in cold climate zones, since it does not freeze (although extremes of cold temperature appear not to damage naloxone [ 82 ]).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Naloxone has been shown to be stable when frozen and thawed between the temperatures of −20 to 4°C or at high temperatures of 80°C. 2 Although naloxone dosage forms normally carry an expiry date of 2 years, a recent study showed that naloxone for injection that had been expired for 30 years still contained more than 90% of active naloxone with limited degradation. 3 Pharmacists should routinely offer replacement kits to patients as their kits expire.…”
Section: Does Naloxone Break Down If It Is Not Stored Properly?mentioning
confidence: 99%